The complete guide to climate change [electronic resource] - Dawson, Brian , 1958-; Spannagle, Matt (Routledge, 2009)
Chapters arranged in alphabetical format cover the scientific, geographical and socio-political issues involved in study of the environment and the human effect upon it. Topics include: environmental science; the carbon cycle and the greenhouse gases; the impacts of climate change on life, land and sea; mitigation strategies from carbon capture to carbon taxes; the Kyoto Protocol and UNFCCC; and renewable fuel